Postpneumonectomy esophageal compression: an unusual complication - YILDIZELİ, BEDRETTİN (ELSEVIER SCIENCE BV, 2005)
We report a case of postpneumonectomy esophageal compression with a complaint of dysphagia. In addition to the bronchial compression seen in postpneumonectomy syndrome, other anatomic structures, such as the esophagus, can also be affected by the extreme mediastinal shifting, and possibly be corrected by placement of prosthetic devices into the ipsilateral hemithorax, or with a stent placement. (c) 2005 Published by Elsevier B.V.
Keywords: postpneumonectomy; esophagus; compression; late complication